Nursing care in patients with HELLP syndrome (Research, Society and Development, 2021)
HELLP syndrome is characterized by primary diagnosis of pre-eclampsia, characterized by the occurrence of elevated blood pressure during pregnancy around the 20th week of pregnancy, accompanied by edema and proteinuria. HELLP syndrome is very serious and increases the risk of death for both the fetus and the pregnant woman. The main objective of this study is to describe nursing care for pregnant women with HELLP syndrome and, more specifically, to describe the main complications of HELLP syndrome in pregnant women. The study was carried out through a literature review with a descriptive and qualitative approach. The main nursing care measures for pregnant women with HELLP identified in the literature analyzed were monitoring respiratory rate, oxygen saturation, urinary output, and patellar reflexes, maintaining rest, weighing daily, performing hydroelectrolyte control and controlling fetal heart rate. HELLP syndrome can present cerebrovascular complications, hemorrhage, pulmonary edema, retinal detachment, hematoma/hepatic, acute renal failure, liver failure, coagulopathy failure, placental detachment, sepsis, platelet activation, elevated serum oxytocin levels, sinusoidal obstruction and hepatic infarction, hepatic hemorrhage, uterine contractions, convulsions, and hemolysis.